Vaccine discussions in pregnancy: interviews with midwives to inform design of an intervention to promote uptake of maternal and childhood vaccines - Jessica Kaufman; Katie Attwell; Yvonne Hauck; Saad B. Omer; Margie Danchin (Taylor & Francis Group, 2019)
Presumptive and Motivational Interviewing communication styles have successfully promoted childhood and adolescent vaccination to parents, but less is known about effective communication approaches during pregnancy to promote maternal vaccination and childhood vaccines. In Australian public antenatal settings, midwives provide a substantial proportion of care and are highly accessed and trusted sources of vaccine information for expectant parents. However, there are no evidence-based interventions incorporating communication strategies and resources for midwives to optimize discussions and promote acceptance of maternal and childhood vaccines. This study aimed to gather qualitative data from midwives to inform the design of a feasible and acceptable vaccine communication intervention package building on an evidence-based model utilized with US obstetricians. We explored midwives' attitudes and values regarding maternal and childhood vaccination, their perceived role in vaccine advocacy and delivery, and barriers and enablers to implementation of a potential communication intervention. We recruited 12 midwives for semi-structured interviews at two Australian tertiary public hospitals (one with antenatal vaccines onsite, one without). Interviews were analyzed using thematic template analysis. Midwives supported vaccination but expressed varied views regarding its centrality to their role. Most reported receiving minimal or no training on vaccine communication. Their communication practices focused primarily on vaccine information provision rather than persuasion, although some midwives shared personal views and actively encouraged vaccination. More vaccine and communication training and resources were requested. Findings highlight the need for communication tools that align with midwifery standards for practice to support midwives to address parents' questions and concerns about maternal and childhood vaccines.